Relationship between perioperative semaglutide use and residual gastric content: A retrospective analysis of patients undergoing elective upper endoscopy - Silveira, Saullo Queiroz; da Silva, Leopoldo Muniz; de Campos Vieira Abib, Arthur; de Moura, Diogo Turiani Hourneaux; de Moura, Eduardo Guimarães Hourneaux; Santos, Leonardo Barbosa; Ho, Anthony M.-H.; Nersessian, Rafael Souza Fava; Lima, Filipe Lugon Moulin; Silva, Marcela Viana; Mizubuti, Glenio B. (Journal of clinical anesthesia, 2023)
Semaglutide is a long-acting glucagon-like peptide-1 receptor agonist used for management of type 2 diabetes and/or obesity. To test the hypothesis that perioperative semaglutide use is associated with delayed gastric emptying and increased residual gastric content (RGC) despite adequate preoperative fasting, we compared the RGC of patients who had and had not taken semaglutide prior to elective esophagogastroduodenoscopy. The primary outcome was the presence of increased RGC. Single-center retrospective electronic chart review. Tertiary hospital. Patients undergoing esophagogastroduodenoscopy under deep sedation/general anesthesia between July/2021–March/2022. Patients were divided into two (SG = semaglutide, NSG = non-semaglutide) groups, according to whether they had received semaglutide within 30 days prior to the esophagogastroduodenoscopy. Increased RGC was defined as any amount of solid content, or > 0.8 mL/Kg (measured from the aspiration/suction canister) of fluid content. Of the 886 esophagogastroduodenoscopies performed, 404 (33 in the SG and 371 in the NSG) were included in the final analysis. Increased RGC was observed in 27 (6.7%) patients, being 8 (24.2%) in the SG and 19 (5.1%) in the NSG (p < 0.001). Semaglutide use [5.15 (95%CI 1.92–12.92)] and the presence of preoperative digestive symptoms (nausea/vomiting, dyspepsia, abdominal distension) [3.56 (95%CI 2.2–5.78)] were associated with increased RGC in the propensity weighted analysis. Conversely, a protective [0.25 (95%CI 0.16–0.39)] effect against increased RGC was observed in patients undergoing esophagogastroduodenoscopy combined with colonoscopy. In the SG, the mean time of preoperative semaglutide interruption in patients with and without increased RGC was 10.5 ± 5.5 and 10.2 ± 5.6 days, respectively (p = 0.54). There was no relationship between semaglutide use and the amount/volume of RGC found on esophagogastroduodenoscopy (p = 0.99). Only one case (in the SG) of pulmonary aspiration was reported. Semaglutide was associated with increased RGC in patients undergoing elective esophagogastroduodenoscopy. Digestive symptoms prior to esophagogastroduodenoscopy were also predictive of increased RGC. •Semaglutide, a GLP-1 agonist, has been associated with delayed gastric emptying.•5.1% of patients not using semaglutide had increased residual gastric content (RGC).•24.2% of patients taking semaglutide perioperatively had increased RGC (p < 0.001).•Presence of pre-endoscopy digestive symptoms was also associated with increased RGC.•Interval of preoperative semaglutide cessation was not predictive of increased RGC.